79 Effective cardioprotection against anthracycline cardiotoxicity in isolated cardiomyocytes and rabbits is based on dexrazoxane interaction with topoisomerase II beta instead of iron chelation by its metabolite ADR-925. (May 2019) - Jirkovsky, Eduard; Jirkovska, Anna; Bavlovic-Piskackova, Hana; Skalicka, Veronika; Pokorna, Zuzana; Karabanovich, Galina; Brazdova, Petra; Lencova-Popelova, Olga; Mazurova, Yvona; Adamcova, Michaela; Roh, Jaroslav; Sterbova-Kovarikova, Petra; et al.
Abstract : Introduction: Anthracyclines (ANT; e.g. doxorubicin, epirubucin or daunorubicin) are still indispensable part of modern chemotherapy regiments, despite of their well-known risk to induce cardiotoxicity leading even to heart failure. Thus, there is a need for effective cardioprotective strategy. Dexrazoxane (DEX) is the only clinically approved drug clearly effective both in clinics and clinically relevant experimental models. However, mechanisms of ANT-cardiotoxicity induction as well as DEX protection are not elucidated yet. Traditionally, ANTs have been believed to induce iron-catalyzed oxidative damage to cardiomyocytes. DEX should prevent this via its metal-chelating metabolite ADR-925, but direct evidence is missing. This paradigm has been recently challenged by topoisomerase IIβ (TOP2B) hypothesis of ANT cardiotoxicity. Hence, the aims of this study were to examine if ADR-925 is really the protective agent in DEX-afforded cardioprotection against daunorubicin (DAU) cardiotoxicity, along with the involvement of TOP2B interaction in this process. Methods: Firstly, a pharmacokinetic studies were employed to set up ADR-925 doses ensuring same or even higher exposition of isolated rat neonatal ventricular cardiomyocytes (NVCMs) and rabbits' heart than after endogenously formed ADR-925 after DEX administration. Cardioprotective effectcs of DEX and ADR-925 (both in 10–100 uM) were compared using NVCMs treated with DAU (1.2 uM). In rabbits (n=50), cardiotoxicity was induced with DAU (3 mg/kg IV, once weekly/10 weeks). Prior to each DAU dose, ADR-925 was administered in two schedules (60 mg/kg 30-min-infusion alone or with additional the same s.c. bolus dose after 2 hrs). Cardiotoxicity markers, LV function and interaction with TOP2B were compared to effects of DEX pre-treatment (60 mg/kg IP). Results: ADR-925 administration did not provide any meaningful cardioprotection against ANT cardiotoxicity in NVCMs. Regardless various administration schedule in rabbits, ADR-925 did not protect against DAU-induced mortality due to end-stage heart failure, decrease of LV function (dP/dtmax and LVFS), increase of cTnT levels, ANP or BNP mRNA as well as histopathological changes. This sharply contrasted with remarkable cardioprotective effects of DEX. Further experiments documented that the parent compound can inhibit and deplete TOP2B and prevent DAU-induced genotoxic damage in cardiomyocytes in contrast to ADR-925. Conclusion: The present investigation strongly encourages the shift of mechanistic paradigm in clinically translatable cardioprotection against anthracycline cardiotoxicity - from metal chelation and protection from direct oxidative damage towards a TOP2B interaction. This study was supported by the Czech Science Foundation [Grant n. 18–08169S], the Charles University Research Program PROGRES [Grant n. Q40/5] and by the project EFSA-CDN (No. CZ.02.1.01/0.0/0.0/16_019/0000841) co-funded by ERDF. Conflict of Interest: None declared